All Days 2012
DOI: 10.2118/157426-ms
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Various Chelates that are used in the Oilfield and Potential Damage Due to their Decomposition Products

Abstract: Chelating agents are used to remove various inorganic scales, including sulfates and carbonates. They are also used as stand-alone stimulation fluids and as iron control agents during acidizing treatments. The main chelating agents used in the field, include: ethylenediaminetetraacetic acid (EDTA), nitrilotriacetic acid (NTA), N-(hydroxyethyl)-ethylenediamineteriaacetic acid (HEDTA), and recently, L- glutamic acid-N, N diacetic acid (GLDA). One of the concerns with these chelates is their thermal stability at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The chelate concentration was measured by titration with a ferric chloride solution (Sokhanvarian et al 2012). Filtration with 1 m pore size filter paper was used to separate solid particles.…”
Section: Methods Used To Analyze the Well Flowback Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…The chelate concentration was measured by titration with a ferric chloride solution (Sokhanvarian et al 2012). Filtration with 1 m pore size filter paper was used to separate solid particles.…”
Section: Methods Used To Analyze the Well Flowback Samplesmentioning
confidence: 99%
“…These products are glutaric and iminodiacetic acids (Fig. It should be also noted that hydroxyglutaric and iminodiacetic acids were previously identified as a decomposition products for H 4 GLDA (Sokhanvarian et al 2012). Peak for retention time 17.33 minutes wasn't fully interpreted but it most probably presents heavy hydrocarbons.…”
Section: Analysis Of Organic Materials Present In the Well Flowback Samentioning
confidence: 99%
See 2 more Smart Citations
“… 42 Ethylenediaminetetraacetic acid (EDTA), hydroxyethyl ethylene diamine triacetic acid (HEDTA), hydroxyethyl iminodiacetic acid (HIDA), glutamic acid di-acetic acid (GLDA), diethylenetriamine pentaacetic acid (DTPA), nitrilotriacetic acid (NTA), and methylglycinediacetic acid (MGDA) are considered common examples for the chelating agents in field descale operations. 43 A study was performed to evaluate the dissolution efficiency for DTPA (20 wt %) with a catalyst (9 wt % potassium carbonate) to dissolve the pyrite (FeS 2 ) scale precipitation, and results showed that 85% of the scale was dissolved at 70 °C and a time of 48 h. 44 , 45 Nitrilotriacetic acid (NTA) is an additional example of the chelating agents that provides a high biodegradability. 46 However, using the chelating agents in the descale treatment is not considered the optimum solution as they are expensive chemicals and further experimental work is needed to determine the optimum pH, solution concentration, treatment time, and thermal stability.…”
Section: Scale Removalmentioning
confidence: 99%